Padec pri varovanju s plezalno vrvjo - Mair, Peter (Medicinski razgledi, 2004)
Based on experimental data, it is widely believed that any extended climbing rope fall may cause life-threatening injuries when using a sit harness alone. This is mainly due to the danger of thoraco-lumbar spinal and visceral abdominal injuries secondary to hyperextension trauma, as well as the risk of a "head down" position during suspension. The aim of this retrospective study was to clarify whether the pattern of injury suggested by experimental data isindeed found in real life falls and whether the type of harness used contributes to morbidity and mortality in climbing accident victims. A total of 57 climbers with a history of a fall into the climbing rope were analysed, 41 using a sit harness alone and 16 using a combination of sit and chest harness. Neither a disruption of the thoraco-lumbar spinal nor abdominal visceral injuries secondary to hyperextension trauma were found in any of our victims using a sit harness alone, despite long falls up to 65 meters. The pattern and severity of injury were not different in climbers using a sit harness alone when compared to those using a combination of sit and chest harness. "Head first" position was common during the fall (33% of all cases), but without any correlation to the type of harness used. "Head down" position after the fall during suspension was less common and found only when no chest harness was used. There was a peak of life threatening injuries and multi-system-trauma cases in routes of low difficulty, the pattern of injury indicating rock contact during the fall as the underling mechanism responsiblefor these injuries. Taken together, we did not find any evidence that the type of harness used significantly influences the pattern or severityof injury in rock climbing accidents. Our data indicate that severe and life threatening injuries in rock climbing accidents are predominantly dueto rock contact during the fall and are more common in routes of low difficulty.
Keywords: Mountaineering; Alpinizem; Nesrečni padci; Accidental Falls; Protective Devices; Urgentne, medicinske službe; Zaščitni pripomočki; Emergency Medical Services; padci; plezalna vrv; poškodbe